Brand management in a situation of an economic crisis: Methods of strengthening the brand value in the scope of emerging markets. Issue 4 (12th September 2016) - Drewniak, Rafał; Karaszewski, Robert
Abstract : Purpose: The purpose of this paper is to present modern marketing tools used by today's businesses to maintain or strengthen the value of their brands in the conditions of deteriorating economic situation. The specific purpose is an analysis of activities that might be attempted by companies in emerging markets in order to increase the strength of their brands. Design/methodology/approach: The paper presents the determinants of the development of brand value. An analysis has also been made of activities connected with the development of the brand based on the experience of the best brands in the world. Considerations are based on secondary sources, from national and international journals, books, magazines and specialist reports, as well as were supported by research results of the most valuable brands in the world. Findings: The paper provides the insight of marketing activities, that may favor building brand value in the time of recession. It was suggested that recession may be a good time for some companies to invest in the brand. However, today's competition conditions are forcing companies to used more modern marketing techniques in order to build a positive brand image. In addition, customers increasingly expect to be able to engage in brand and wish to influence its image. Practical implications: The paper includes implications for companies in emerging markets, through which it is possible to effectively manage brand value in the time of crisis. These proposals are an important course of action for companies from emerging markets, which tend to increase the strength of its brand. Originality/value: Due to the fact that the considerations in the paper relate to general proposals for action, the results can constitute a starting point for in-depth research in the future. An interesting issue would be to assess the effectiveness of the proposed activities in emerging markets.